2020
DOI: 10.5603/imh.2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing of a selection of seafarers in Eastern Adriatic Sea during the COVID-19 pandemic 2020

Abstract: Background: Work-related stress among seafarers is well known but a suspected excess of work-related stress due to the COVID-19 so far has not been published. The aim of the study was to evaluate the well--being of the seafarers during the outbreak of COVID-19 pandemic and their evaluation of the precautions taken by the shipping companies. Materials and methods: Seventy-two seafarers completed the General Health Questionnaire (GHQ12) with three extra questions on how the COVID-19 precautions were taken on boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…In response to other items, half of the seafarers did not feel safe performing their jobs and 60% did not think that every precaution had been taken to ensure their health at work due to the pandemic. Another 30% suffered from insomnia to the extent of becoming concerned, while 26% reported being unhappy and depressed during their latest tour of duty [23]. In response, a combination of person-focused and organization-focused prevention approaches has been advocated as the most promising for alleviating job stress in the workplace at sea (ISWAN) [24].…”
Section: Seafarers' Mental Health and Associated Factorsmentioning
confidence: 99%
“…In response to other items, half of the seafarers did not feel safe performing their jobs and 60% did not think that every precaution had been taken to ensure their health at work due to the pandemic. Another 30% suffered from insomnia to the extent of becoming concerned, while 26% reported being unhappy and depressed during their latest tour of duty [23]. In response, a combination of person-focused and organization-focused prevention approaches has been advocated as the most promising for alleviating job stress in the workplace at sea (ISWAN) [24].…”
Section: Seafarers' Mental Health and Associated Factorsmentioning
confidence: 99%
“…[46]. A survey of 72 seafarers using the General Health Questionnaire (GHQ12) confirmed excess work-related stress in the pandemic situation although an earlier study of 350 seafarers with higher resilience, longer experience and greater support at work reported lower levels of stress at sea [47].…”
Section: Covid-19 and Seafarers' Well-beingmentioning
confidence: 99%
“…Since they have limited access to medical and psychosocial distress services, it seems that ocean shipping and its employees are more vulnerable than the other shipping sectors or even other occupations during the COVID-19 pandemic period. Despite all mentioned above, at the time of writing, just one published study with a minimal sample size on seafarers' well-being during COVID-19 has been found, which might not capture the full picture of such a major health emergency [12]. Besides, there has been no published study about seafarers' overall and psychosocial distress status on ocean-going vessels.…”
Section: Introductionmentioning
confidence: 99%